Significant methane ebullition from alpine permafrost rivers on the East Qinghai–Tibet Plateau - Zhang, Liwei; Xia, Xinghui; Liu, Shaoda; Zhang, Sibo; Li, Siling; Wang, Junfeng; Wang, Gongqin; Gao, Hui; Zhang, Zhenrui; Wang, Qingrui; Wen, Wu; Liu, Ran; et al. (Nature geoscience, 2020)
Inland waters are large sources of methane to the atmosphere. However, considerable uncertainty exists in estimating the emissions of this potent greenhouse gas from global streams and rivers due, in part, to a lack of direct measurements in the high-altitude cryosphere and poor accounting for ebullition. Here we present methane concentrations and fluxes over three years in four basins on the East Qinghai–Tibet Plateau. Methane ebullition rates decrease exponentially whereas diffusion declines linearly with increasing stream order. Nonetheless, the average ebullition rate (11.9 mmolCH 4 m −2 d −1 ) from these streams and rivers—which have large organic stocks in surrounding permafrost, abundant cold-tolerant methanogens, shallow water depths, and experience low air pressure—were six times greater than the global average and reached a maximum of 374.4 mmolCH 4 m −2 d −1 . Upscaled total emissions from sampled third- to seventh-order waterways of the East Qinghai–Tibet Plateau are estimated to be 0.20 TgCH 4 yr −1 , 79% of which was attributed to ebullition. These methane emissions are approximately 20% of CO 2 emissions (2.70 TgCO 2 yr −1 ) in terms of carbon release and two times greater in terms of CO 2 -equivalent emissions. When upscaled to first- to seventh-order waterways, we estimate emissions of 0.37–1.23 TgCH 4 yr −1 . Our findings demonstrate that high-elevation rivers on the Qinghai–Tibet Plateau are hotspots of methane delivery to the atmosphere. The large ebullitive fluxes, which constitute a substantial fraction of global fluvial methane emissions, reveal a positive feedback between climate warming, permafrost thaw and methane emissions. High-elevation rivers in permafrost of the East Qinghai–Tibet Plateau are hotspots of methane emissions, according to measurements of methane fluxes in the region.